ICT facilities and Orang Asli education at Royal Belum, Gerik, Perak - Dziyauddin, Rudzidatul Akmam (2015)
An effective teaching and learning using Information and Communication Technology (ICT) is necessary to facilitate students to the world of knowledge at their fingertips. The use of ICT essentially leads to significant impact on a condusive learning environment and also on the students’ achievements. In Malaysia, the students come from different background and ethnics, which include orang Asli. The urban students might face less difficulties in accepting the ICT in their lessons. A question then raised regarding the readiness of the Orang Asli students, particularly in remote areas, like Royal Belum, Malaysia. This paper investigates the readiness of the primary students, namely from the Jahai group, in Royal Belum on the use of ICT devices, such as notepad and laptop. In addition to that, we studied the internet facilities and its connectivity at the schools, including some other related issues. Outcome of the observations show positive readiness of Orang Asli students in using ICT devices. Nevertheless, a substantial effort from the ICT teachers seems crucial to the effective delivery of the ICT syllabus. Additionally, the schools suffer with slow connectivity as the data rate of 20 Mbps needs to be shared with other nearby schools. This has affected the students’ learning and also the teachers’ daily tasks, for instance, in meeting District Education Department (PPD) requirements regarding uploading marks online. Therefore, it is appropriate for the government agencies to search some initiatives in solving the current issues.